A comparative assessment of endothelium from pseudophakic and phakic donor corneas stored in organ culture. Issue 4 (1st April 2002) - Meier, F M; Tschanz, S A; Ganzfried, R; Epstein, D
Abstract : Aims: To evaluate the endothelial quality of corneas obtained from pseudophakic donors and to compare the data with matched phakic controls. Methods: Corneas from eyes with posterior chamber intraocular lenses (PCIOLs) and corneas from phakic eyes (controls) were stored for 1–2 weeks in organ culture and then examined after staining with Alizarin red S. The corneas were divided into two groups according to the duration of storage. Endothelial cell density, the percentage of hexagonal cells, and the coefficient of variation (CV) were determined. Results: There was no statistically significant difference between the 14 PCIOL corneas and the 13 controls stored in organ culture for 7 days for any of the three parameters studied. The mean cell density was 2155 (SD 529) cells/mm 2 in the PCIOL corneas and 2118 (453) cells/mm 2 in the controls (p=0.85). The mean percentage of hexagonal cells was 52% (8%) and 58% (7%), respectively (p=0.06). The mean CV was 0.32 (0.18) in the pseudophakic corneas and 0.39 (0.18) in the controls (p=0.33). Moreover, there was no significant difference between the PCIOL corneas and the controls stored for up to 2 weeks. Conclusions: The corneal endothelium from eyes with PCIOLs appears to be similar to that of phakic eyes after 1–2 weeks in organ culture. This finding suggests that corneas from pseudophakic eyes should not routinely be disqualified for transplantation. The use of at least some pseudophakic corneas may substantially increase the potential donor pool.